nhớ chèn lệnh [tex]
*C1:nếu [TEX] log_2(x-\sqrt{x^2-1})=0[/TEX]\Rightarrow x= ......
nếu [TEX]log_2(x-\sqrt{x^2-1}) \not=\ 0[/TEX]
pt\Leftrightarrow[TEX]log_3(x+\sqrt{x^2-1})=\frac{log_6(x-\sqrt{x^2-1})}{log_2(x-\sqrt{x^2-1})}[/TEX]
\Leftrightarrow[TEX]log_3(x+\sqrt{x^2-1})=log_62[/TEX]\Leftrightarrow[TEX]x+\sqrt{x^2-1}=3^{log_62}[/TEX]
*C2 :hoặc có thể đặt [TEX]log_2(x-\sqrt{x^2-1})=t \Rightarrow x-\sqrt{x^2-1}=2^t [/TEX]
\Rightarrow [TEX]x+\sqrt{x^2-1}=\frac{1}{2^t}=2^{-t}[/TEX]
phương trình thành [TEX] -t^2log_32=t.log_62[/TEX]
\Leftrightarrow t=0 hoặc [TEX]t=\frac{log_62}{log_32}=log_63[/TEX]
thay vào giải phương trình bậc 2